2020
DOI: 10.3168/jds.2019-17862
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Antimicrobial potential of Lactobacillus plantarum strains isolated from Slovak raw sheep milk cheeses

Abstract: The objective of this study was to screen Lactobacillus plantarum strains isolated from the traditional Slovak raw sheep milk cheese for their inhibitory potential. Seventy-two strains were obtained from samples of raw sheep milk and raw sheep milk cheeses collected from April 2017 to September 2018, in 23 geographical areas of Eastern Slovakia, by inoculation of de Man, Rogosa, and Sharpe agar plates (Oxoid, Basingstoke, UK). Using both the genus-and species-specific PCR methods, 43 strains were identified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 9 publications
2
10
0
1
Order By: Relevance
“…Lpb. plantarum strains are known to produce a wide range of antibacterial compounds, including bacteriocins, organic acids, ethanol, diacetyl, and H 2 O 2 [ 28 , 29 , 30 ]. Furthermore, antibacterial substances produced by LAB are generally recognized as non-toxic and non-irritant components because they are naturally degraded in the body or the environment [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lpb. plantarum strains are known to produce a wide range of antibacterial compounds, including bacteriocins, organic acids, ethanol, diacetyl, and H 2 O 2 [ 28 , 29 , 30 ]. Furthermore, antibacterial substances produced by LAB are generally recognized as non-toxic and non-irritant components because they are naturally degraded in the body or the environment [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of lactobacilli in raw milk has been confirmed by several studies, including Vataščinová et al, where in 23 geographical areas of Eastern Slovakia, 43 strains have been identified as Lactobacillus sp. [31]. However, the high nutrient content of raw milk during storage makes it a suitable medium for a large number of other microorganisms, such as C. perfringens, S. aureus, E. coli, L. monocytogenes, Salmonella spp., Bacillus cereus, Streptococcus sp., etc., which develop rapidly in it and cause its deterioration [32].…”
Section: Discussionmentioning
confidence: 99%
“…In Slovakia, dairy products made from ewe's milk include, e.g., traditional cheeses such as "parenica", "korbáčik" "oštiepok", and Liptauer bryndza, and also ewe's milk lump cheese, either fresh or smoked [3][4][5]. "Parenica", "korbáčik" "oštiepok" and Liptauer bryndza, as well as Oravian korbáčik cheese and Zázrivá korbáčik cheese, were designed to be PGI products, meaning products with protected geographical indication [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These various microbiota can play vital roles in the development of the organoleptic properties of cheese, nutrient composition, shelf-life, and safety [8]. The bacterial population in those cheeses has been already studied [2,5] using the standard microbiological method.…”
Section: Introductionmentioning
confidence: 99%